If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -12 = 10 + -2x Reorder the terms: -12 + 6x = 10 + -2x Solving -12 + 6x = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12 + 6x + 2x = 10 + -2x + 2x Combine like terms: 6x + 2x = 8x -12 + 8x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 -12 + 8x = 10 + 0 -12 + 8x = 10 Add '12' to each side of the equation. -12 + 12 + 8x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + 8x = 10 + 12 8x = 10 + 12 Combine like terms: 10 + 12 = 22 8x = 22 Divide each side by '8'. x = 2.75 Simplifying x = 2.75
| 4x+7x-3=6x+3x+5 | | 2a^2-5a+2=0 | | X(2X-2)+X(7X-3)=(9X+5)(X-1) | | 10a=5(a-3)+15 | | 6x-12=6-2x+4 | | 2.5(2x-4)=4(4x-4)+x | | -10+4(-2x+3)=-22 | | -9-y=6 | | 14+27m=28+20m | | 126=3n+6(-4n-7) | | 3(m+3)=18 | | 1250+x(25)=2500 | | 5n+3=n-25 | | 83d-34d=-49 | | 7(h-5)= | | 116=-2(7k-2) | | -6=x-11 | | -40x^2+1140x-7020=0 | | 9-y=6 | | 25-2(5.8-5)=19 | | -3(n-90)=27 | | n+n+2+n+4+n+6+n+8=-9 | | 3(5x+4)=6(x+2) | | 8(.25+x)=18 | | 6x-y=-8 | | 6(v+1)-10=4(v-1)+2v | | 8b-4b+15=63 | | 5y-4/3=7 | | -x^2+2x-35=y | | 20-16p=20-16p | | n+(n+8)=3(n+6)-1 | | 7-2k=8-5k |